855Performance of a multisensor icd algorithm in heart failure patient management. (18th June 2020) - Santini, L; Bianchi, V; Dello Russo, A; Calo, L; Pecora, D; Mahfouz, K; Favale, S; Petracci, B; Costa, A; Cipolletta, L; De Ruvo, E; La Greca, C; et al.
Abstract: Funding Acknowledgements: No funding Background: The HeartLogic index combines data from multiple implantable cardioverter-defibrillator (ICD)-based sensors and has proved to be a sensitive and timely predictor of impending heart failure (HF) decompensation. Purpose: To describe a multicenter experience of remote HF management of patients who received a HeartLogic-enabled ICD or cardiac resynchronization therapy ICD (CRT-D). Methods: The HeartLogic feature was activated in 104 patients (76 male, 71 ± 10 years, left ventricular ejection fraction 29 ± 7%). In accordance with a standardized follow-up protocol, remote data reviews and patient phone contacts were performed monthly and at the time of HeartLogic alerts (when the index crossed the nominal threshold value of 16), to assess the patient decompensation status. In-office visits were performed every 6 months or when deemed necessary. Results: During a median follow-up of 13[11-18] months, 100 HeartLogic alerts were reported (0.82 alerts/pt-year) in 53 patients. 60 HeartLogic alerts were judged clinically meaningful (i.e. associated with worsening of HF or resulted in active clinical actions). Specifically, multiple associated conditions were reported: 45 (75%) symptoms or signs of clinical deterioration of HF, 13 (22%) discontinuations or reductions of prescribed HF therapy, 11 (18%) declines in CRT percentage (with or without new onset atrial fibrillation), 8 (13%) recurrences of previous HF events. For 48 out of 60 alerts the clinician was not previously aware of the condition. Of these, 43 alerts triggered multiple clinical actions. Alert-triggered actions were: 30 (70%) diuretic dosage increases, 15 (35%) other drug adjustments, 6 (14%) HF hospitalizations, 3 (7%) device reprogramming/revisions, 1 (2%) cardioversion, 1 (2%) patient education on therapy adherence. Out of 40 non-clinically meaningful alerts (0.33 alerts/pt-year), 8 (20%) were associated with non-HF therapy changes or interventions, 3 (8%) with pulmonary events, 29 (72%) remained unexplained. The overall number of HF hospitalizations was 16 (rate 0.13 hospitalizations/pt-year). Five HF hospitalizations were not preceded by HeartLogic alert (0.04 hospitalizations/pt-year). Conclusions: The HeartLogic index provided clinically meaningful information and allowed to remotely identify relevant HF related clinical conditions, with a low rate of unexplained detections and undetected HF events. In this experience, remote monitoring using HeartLogic alerts allowed to drive HF care and take effective clinical actions.